Stromal vascular fraction in canine osteoarthritis: advantages, applications, and insights for veterinary practitioners - Wang, Aline Yen Ling; Aviña, Ana Elena; Liu, Yen-Yu; Kao, Huang-Kai (Frontiers in Veterinary Science, 2025)
Canine osteoarthritis (OA) stands as a prevalent and excruciating joint condition that represents a promising application of stromal vascular fraction (SVF) treatment. In this review, we discuss the multi-factorial advantage of SVF cited as anti-inflammatory, regenerative, and angiogenic, all of which improve the complex pathology of OA. The heterogeneous cellular structure of SVF allows it to achieve joint improvement through both cell-based tissue restoration and signaling functions that benefit joint health. Veterinary practitioners need to consider essential aspects for clinical practice including patient selection criteria together with specific dosage recommendations along with additional therapies like platelet-rich plasma. Existing clinical data shows that SVF reduces pain while helping restore joint functions while practitioners face challenges when standardizing protocols and evaluating long-term safety aspects. Future research initiatives aim to translate advanced technologies including bioactive scaffolds, gene editing, and artificial intelligence which show promise for enhancing therapeutic results. This review integrates existing information about SVF while enlightening veterinarians about the gap areas to assist them make informed decisions when implementing SVF in practice. SVF represents a huge step forward in veterinary regenerative medicine because it enables better management of OA as well as other orthopedic applications.